Analisis Prosedur Pemeriksaan Multislice Computed Tomography Urografi pada Pasien dengan Klinis Urolithiasis - Fani Susanto; Hernastiti Sedya Utami; Lutfatul Fitriana (Jurnal Imejing Diagnostik (JImeD), 2022)
Backgroud: Urolithiasis is the formation of crystalline mineral deposits in the urinary system. Examination of MSCT Urographic with and without administration of intravenous contrast media is used to detect various abnormalities in the urinary tract area. This study aims to analyze MSCT Urographic examination procedures in patients with clinical Urolithiasis at the Radiology Unit of Premier Bintaro Hospital.Methods: Type of study is qualitative with a case study approach. Collection data was conducted at the Radiology Unit of Premier Bintaro Hospital with specialists and documentation observation methods, interviews with radiographers and radiology. Data processing and analysis are carried out descriptively related to the results of observation, interviews and documentation so that conclusions and suggestions can be drawn.Results: Urographic MSCT examination in patients with clinical Urolithiasis performed with patient preparation by laboratory check to check kidney function (urea and creatinine), examination was performed using the MSCT rutine protocol with the addition of contrast media by scanning the unenhance phase, enhance phase includes arterial phase, phase portal vein and delay phase which is 7 minutes and 15 minutes with prone patients in the kidney vesica urinaria area, and post void. The addition of contrast media is intended to show enhancement and narrowing of the urinary tract.Conclusion: Examination of MSCT Urography in patients with clinical Urolithiasis in the Radiology Unit of Premier Bintaro Hospital is done with patient preparation laboratory check, the protocol is done by scanning the unenhance and enhance phases.